(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research comprehensively explores Stephenie Meyer’s literary works from a dual perspective. The first analysis delves into the intricate interplay between nature and narrative in Life and Death, a gender-swapped reinterpretation of the Twilight series. Through an exhaustive examination of setting, characters, and thematic elements, the study unveils nature’s transformation from a backdrop to a dynamic force intricately interwoven with characters’ emotions and experiences. Meyer’s strategic use of nature as a metaphorical canvas mirrors inner worlds, emotional dynamics, and pivotal moments, with recurring natural environments paralleling characters’ transformations and relationships. Furthermore, the study posits that interactions involving vampire characters and the Quileute wolves emphasize a thematic focus on balance and interconnectedness between humanity and nature. The second facet of the research centers on ecological elements within Life and Death, analyzing the significance of the setting, character-environment interactions, ecological imbalances, and the depiction of the vampire lifestyle in relation to ecological themes. This inquiry demonstrates how supernatural fiction can effectively convey ecological messages, deepening our understanding of environmental themes in literature and popular culture.